2023
DOI: 10.1590/1678-6971/eramd230007.pt
|View full text |Cite
|
Sign up to set email alerts
|

Como mensurar a resiliência organizacional? Validando um modelo simplificado

Alã Y. P. Santos,
Renata G. Spers

Abstract: Resumo Objetivo: Este estudo buscou analisar os elementos que compõem a resiliência das organizações diante de um evento disruptivo, utilizando como contexto a crise provocada pela Covid-19. Originalidade/valor: O estudo da resiliência organizacional nos ajuda a teorizar com mais precisão o ajuste e a adaptação organizacional em ambientes cada vez mais complexos e difíceis de ser compreendidos. Entretanto, embora a sua investigação tenha demonstrado ser algo promissor, o seu conceito ainda necessita de maior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the field of administration, this study demonstrated how resilience can be measured and assessed across different sectors. Additionally, this research can be considered an advancement in the development of the Organizational Resilience field, as early research reported the lack of quantitative studies and scarce empirical evidence on resilience measures as a gap to be filled (Kantur & Iseri-Say, 2015;Rahi, 2019;Santos & Spers, 2023). For practical applications, the procedures applied in our study resulted in a clear and objective diagnosis of the resilience of firms located in a specific geographic area.…”
Section: Global Assessment Of Resilience Abilitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the field of administration, this study demonstrated how resilience can be measured and assessed across different sectors. Additionally, this research can be considered an advancement in the development of the Organizational Resilience field, as early research reported the lack of quantitative studies and scarce empirical evidence on resilience measures as a gap to be filled (Kantur & Iseri-Say, 2015;Rahi, 2019;Santos & Spers, 2023). For practical applications, the procedures applied in our study resulted in a clear and objective diagnosis of the resilience of firms located in a specific geographic area.…”
Section: Global Assessment Of Resilience Abilitiesmentioning
confidence: 93%
“…The acknowledgment of resilience has compelled organizations to review their business process and capabilities (Bartuseviciene et al, 2022). Unavoidably, the concern about resilience also prompts the discussion of how it can be addressed and measured (Kantur & Iseri-Say, 2015;Santos & Spers, 2023). For Linnenluecke (2017), many companies will likely be unprepared for adverse events unless they explicitly approach resilience in a manageable way, being clear about how resilience is defined, described (variables), assessed, maintained, and improved.…”
Section: Introductionmentioning
confidence: 99%